1995
DOI: 10.1007/bf00173710
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cells containing factor XIII subunit a in benign and malignant buccal lesions

Abstract: In the present study, the distribution pattern and characteristics of cells containing Factor XIII subunit a (FXIII A) have been studied in benign and malignant lesions of human buccal mucosa. Tissues from four irritation fibromas and three squamous cell carcinomas were studied by means of double immunofluorescent staining techniques in which the detection of FXIII A was combined with a reaction with CD14 (recognizing a monocyte/macrophage differentiation marker antigen), Mac 387 (reacting with a special subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…The a-subunit of FXIIIa belongs to a family consisting of several genes that encode for enzymes with a common active-site structure, well conserved among species (17). Accumulating evidence points to an additional role for FXIIIa in prolifera-tion of connective tissues via its expression by invading macrophages (18,19). In this study, we discovered some characteristics of the a-subunit of FXIIIa in fish plasma that are distinct from those of its mammalian counterpart.…”
mentioning
confidence: 76%
“…The a-subunit of FXIIIa belongs to a family consisting of several genes that encode for enzymes with a common active-site structure, well conserved among species (17). Accumulating evidence points to an additional role for FXIIIa in prolifera-tion of connective tissues via its expression by invading macrophages (18,19). In this study, we discovered some characteristics of the a-subunit of FXIIIa in fish plasma that are distinct from those of its mammalian counterpart.…”
mentioning
confidence: 76%
“…In the present study we have shown that TGF-β co-localizes with the blood coagulation and wound healing protein XIII α in fibrotic lesions of carcinoid heart disease. Although the main function of XIII α is the cross-linking of fibrin molecules, it also takes part in wound healing and, as previous research indicated, in fibrotic processes [20, 21]. In this context it is noteworthy that fibrinogen and fibrin have been previously identified in carcinoid plaques [22].…”
Section: Discussionmentioning
confidence: 99%
“…AL has plump FXIIIa+dendritic cells (B). FXnia+ multivacuolated lipoblast-like cells amidst vessels in an angiolipoma in 35 year old male with multiple tumors (C). A-C x 400. sal sinus, a tissue devoid of fat, suggested that both the fat and HPC arose from the same precursor.…”
Section: Discussionmentioning
confidence: 99%
“…Marker studies suggest that FXIIIaH-stromal dendrophages are monocyte/macrophages that differentiate after migrating from the blood (23''^, 24,35,51). However, in utero, appearance of separate FXI-IIa+ and CD34+ dermal and stromal dendritic cells both predate the formation of the bone marrow (16,(25)(26)(27) and both cell types persist in adult stroma (16, 21, 23^, 50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation